Ion regulation of ionic liquid electrolytes for supercapacitors. Issue 5 (12th April 2021) - Feng, Jianze; Wang, Yan; Xu, Yongtai; Sun, Yinglun; Tang, Yu; Yan, Xingbin
Abstract : As a member of the liquid electrolyte family, ionic liquids (ILs) possess distinctive chemical and electrochemical stability, offering a pathway to realize supercapacitors (SCs) with both outstanding energy density and high safety. Abstract : As a member of the liquid electrolyte family, ionic liquids (ILs) possess distinctive chemical and electrochemical stability, offering a pathway to realize supercapacitors (SCs) with both outstanding energy density and high safety. Nevertheless, the rapid development of IL based SCs is largely limited due to the high viscosity and poor ionic conductivity of ILs. One feasible solution, albeit challenging, is implementing ion regulation for IL electrolytes because of the highly adjustable nature of anions and cations. This paper provides an overview of the recent progress in ion regulation for IL-based SCs. We describe the energy storage mechanisms and ion regulation methods of IL electrolytes in electrical double-layer capacitors, with special emphasis on the effects of ion regulation to the electrochemical performance of electrode materials and devices. Moreover, we also discuss challenges in regulating IL-based electrolytes for SCs from personal perspectives, and give future possible directions for constructing superior IL-based electrolytes for the next generation of SCs.